SSOME MODERN ASPECTS OF CATARACT TREATMENT IN CHILDREN - K. B. Pershin; N. F. Pashinova; A. V. Tcherkashina (Вопросы современной педиатрии)
The authors represent their own results of surgical treatment of cataract in children with implantation of various types of intraocular lenses: common Corneal, torus — AcrySof Toric and aspheric — AcrySof IQ. It was established, that post-surgical visual acuity in patients with astigmatism was higher in children with AcrySof Toric lenses implantation in comparison with implantation of common intraocular lenses, which simplifies post-surgical correction and improves the efficacy of amblyopia treatment. Good refraction results were received after implantation of intraocular lenses in children younger than 2 years old, which at the average approximates the agespecific refraction norms in children and creates favourable possibilities of the visual analyzer development according to the growth of the eye-bulb. On the basis of the own experience the authors suggest the algorithm of surgical tactics and optimal terms of treatment of congenital cataract and amblyopia.